2005
DOI: 10.1021/cm050641z
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation of Work Function and Surface Stability: The Case of BaAl4

Abstract: The relationship between the work function (Φ) and the surface stability of compounds is, to our knowledge, unknown, but very important for applications such as organic light-emitting diodes. This relation is studied using first-principles calculations on various surfaces of BaAl4. The most stable surface [Ba terminated (001)] has the lowest Φ (1.95 eV), which is lower than that of any elemental metal including Ba. Adding barium to this surface neither increases its stability nor lowers its work function. BaAl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
1
9
1
Order By: Relevance
“…In contrast, previous work [7] showed that the surface with the lowest work function is also the most stable one, at least for BaAl 4 . From analysis of the results we predicted that this should be a more general feature of complex metals, more specifically of intermetallic compounds with polar unit cells.…”
Section: Introductioncontrasting
confidence: 62%
See 2 more Smart Citations
“…In contrast, previous work [7] showed that the surface with the lowest work function is also the most stable one, at least for BaAl 4 . From analysis of the results we predicted that this should be a more general feature of complex metals, more specifically of intermetallic compounds with polar unit cells.…”
Section: Introductioncontrasting
confidence: 62%
“…The method to calculate the work function of a specific surface is described in Ref. [7]. A bulk calculation provides an accurate E F .…”
Section: Work Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most stable surfaces also had the lowest work functions. [3][4][5] In the case of BaAl 4 , this model correctly predicts a Ba terminated surface that also has the lowest work function; the more electropositive element, i.e., Ba, prefers to reside at the surface and, hence, also induces a dipole moment that tends to lower the work function. The other intermetallics studied, CaAl 4 , LaB 6 , Ca 2 N, and BaAuIn 3 , exhibited similar behavior.…”
Section: Summary and Discussionmentioning
confidence: 75%
“…This was first demonstrated in a computational study for BaAl 4 . 3 The barium terminated ͑001͒ surface has a work function of 1.95 eV, which is lower than that of elemental barium ͑2.32 eV͒. It is even lower than that of any element, which is clearly in contradiction with the alloy effect.…”
Section: Introductionmentioning
confidence: 95%